Evaluation of implementation and effect of primary school based intervention to reduce risk factors for obesity. Issue 7320 (3rd November 2001) - Sahota, Pinki; Rudolf, Mary C J; Dixey, Rachael; Hill, Andrew J; Barth, Julian H; Cade, Janet
Abstract: Objectives: To implement a school based health promotion programme aimed at reducing risk factors for obesity and to evaluate the implementation process and its effect on the school. Design: Data from 10 schools participating in a group randomised controlled crossover trial were pooled and analysed. Setting: 10 primary schools in Leeds. Participants: 634 children (350 boys and 284 girls) aged 7-11 years. Main outcome measures: Response rates to questionnaires, teachers' evaluation of training and input, success of school action plans, content of school meals, and children's knowledge of healthy living and self reported behaviour. Results: All 10 schools participated throughout the study. 76 (89%) of the action points determined by schools in their school action plans were achieved, along with positive changes in school meals. A high level of support for nutrition education and promotion of physical activity was expressed by both teachers and parents. 410 (64%) parents responded to the questionnaire concerning changes they would like to see implemented in school. 19 out of 20 teachers attended the training, and all reported satisfaction with the training, resources, and support. Intervention children showed a higher score for knowledge, attitudes, and self reported behaviour for healthy eating and physical activity. Conclusion: This programme was successfully implemented and produced changes at school level that tackled risk factors for obesity.